2016
DOI: 10.1038/srep26256
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of studies using statins as a reducer for primary liver cancer risk

Abstract: A protective effect of statins on primary liver cancer (PLC) risk has been suggested. However, issues about the dose–response relationship, the protective effect of individual statins, and PLC risk reduction among at-risk populations remain unsolved. Therefore, a meta-analysis was conducted. PubMed and EMBASE were searched for studies providing the risk ratio (RR) on statins and PLC risk. Summary RRs were calculated using a random-effects model. Twenty-five studies were identified. Stain use was significantly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
37
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 59 publications
2
37
0
1
Order By: Relevance
“…Statins may have a role in colorectal cancer chemoprevention by acting at the later stages of progression rather than at the early stages of adenoma initiation and development in the adenoma-carcinoma sequence (Jung et al 2016). A protective effect of statins on primary liver cancer (PLC) was observed, most notably of rosuvastatin (Zhong et al 2016). This protective effect is more pronounced in high-risk populations, is dose-dependent, and persisted in patients with diabetes, hepatitis B or C virus infection.…”
Section: Effect Of Statins In Animal and Human Studiesmentioning
confidence: 83%
See 1 more Smart Citation
“…Statins may have a role in colorectal cancer chemoprevention by acting at the later stages of progression rather than at the early stages of adenoma initiation and development in the adenoma-carcinoma sequence (Jung et al 2016). A protective effect of statins on primary liver cancer (PLC) was observed, most notably of rosuvastatin (Zhong et al 2016). This protective effect is more pronounced in high-risk populations, is dose-dependent, and persisted in patients with diabetes, hepatitis B or C virus infection.…”
Section: Effect Of Statins In Animal and Human Studiesmentioning
confidence: 83%
“…These findings support the suggestion that statins can serve as chemopreventive agents of PLC and reduce the public health burden of this malignancy. Prospective cohort studies with sufficient follow-up duration and large sample size are warranted to address this issue before formally recommending statins in preventing PLC (Zhong et al 2016). Liu et al have shown that lovastatin and fluvastatin did not significantly reduce the lung cancer risk in patients with chronic obstructive pulmonary disease (COPD) .…”
Section: Effect Of Statins In Animal and Human Studiesmentioning
confidence: 99%
“…They concluded that the use of statins decreased the risk of primary liver cancer. Notably, the protective effects of rosuvastatin were higher than those of the other statins (43).…”
Section: Meta Analyses On Statinsmentioning
confidence: 99%
“…Simvastatin is metabolised primarily by CYP3A4, when it is used concomitantly with amiodarone, which is an inhibitor of CYP3A4 enzyme; and interaction between these two drugs (simvastatin and amiodarone) increases hepatotoxicity (42). Another study, meta-analysis was carried out by Zhong et al (43). They investigated the protective effects of statins relative to the risk of primary liver cancer.…”
Section: Meta Analyses On Statinsmentioning
confidence: 99%
“…Розувастатин и аторвастатин (но не другие статины) снижают уровень мочевой кислоты сыворотки крови [39]. Есть данные о том, что применение статинов снижает риск гепатоцел-люлярной карциномы [40,41]. Sahebkar с соавт.…”
unclassified